1996
DOI: 10.1037/0033-3204.33.1.51
|View full text |Cite
|
Sign up to set email alerts
|

Pre-treatment social support and effective psychotherapeutic process: A panel study.

Abstract: This study examined the relationship between social support provided (prior to treatment) by 57 individual psychotherapy patients' significant others and three process components at three points in treatment-the first session, the fifth session, and the sixteenth session. Strong pre-treatment network supports generally were found to have a significant positive association with the therapeutic bond, patient selfrelatedness, and therapeutic realizations in the initial phase of treatment, but were (progressively)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
2
0

Year Published

1999
1999
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 26 publications
1
2
0
Order By: Relevance
“…Although higher pretreatment social support was not associated with increased rates of improvement, higher social support was associated with lower initial symptom levels, a result consistent with a substantial body of research that has linked strong social support to better mental health (Bankoff, 1996; Cohen & Wills, 1985). In the present study, a difference in one standard deviation of pretreatment social support meant a 15‐point difference in pretreatment symptom levels on the OQ‐45.…”
Section: Discussionsupporting
confidence: 78%
“…Although higher pretreatment social support was not associated with increased rates of improvement, higher social support was associated with lower initial symptom levels, a result consistent with a substantial body of research that has linked strong social support to better mental health (Bankoff, 1996; Cohen & Wills, 1985). In the present study, a difference in one standard deviation of pretreatment social support meant a 15‐point difference in pretreatment symptom levels on the OQ‐45.…”
Section: Discussionsupporting
confidence: 78%
“…However, few studies have examined whether other patient characteristics, and especially other interpersonal variables that are also predictors of alliance quality, moderate the associations between the attachment dimensions and the alliance. For example, across multiple psychotherapies for various disorders, patients’ pretreatment social support has been positively associated with the alliance (Bankoff, 1996; Hersoug, Høglend, Havik, von der Lippe, & Monsen, 2009; Hersoug, Monsen, Havik, & Høglend, 2002; Mallinckrodt, 1991; Meier, Donmall, Barrowclough, McElduff, & Heller, 2005), suggesting that patients who have quality, supportive relationships outside of therapy tend to also form more positive relationships with their therapist. Social support is also related to more positive treatment outcomes (for a meta-analysis see Roehrle & Strouse, 2008).…”
mentioning
confidence: 99%
“…Recent research has begun to challenge this assumption. For example, Bankoff (1996) found that emotional neglect predicted less cohesive therapeutic bonds early in therapy, but this effect diminished in the later phase. Similarly, Paivio and Bahr (1998) found that, in an experiential therapy similar to EFT-AS, various types of client interpersonal problems were differentially associated with early and late alliance quality; and none of the client variables predicted outcome.…”
mentioning
confidence: 99%